Densification of food waste compost: Effects of moisture content and dairy powder waste additives on pellet quality - Chew, Kit Wayne; Chia, Shir Reen; Yap, Yee Jiun; Ling, Tau Chuan; Tao, Yang; Show, Pau Loke (Institution of Chemical Engineers, 2018)
Densification of food waste compost through pelletizing is essential to increase the bulk density, expand its storability, provide ease of transportation, as well as to enable easier handling of the compost. Compost in its natural form takes up a lot of space and has a high powder dispersion rate which makes it less safe and difficult to handle. The compression of these composts into pellet forms will reduce the managing issues associated with the natural compost feedstock. In this study, the pelletizing of food waste compost by adjusting the moisture content and dairy powder waste addition was performed to evaluate the pelletization performance. The physical and mechanical properties such as moisture content, bulk density, producibility, particle density, compressive strength and moisture resistance were evaluated for the pelletized compost products. This research indicates that the addition of dairy powder additives containing lactose is very beneficial in improving the pellet production rate as well as the properties of the pellets. The pellets with lactose addition showed better producibility, better compressive strength and higher density. The presence of more solid bridges was also observed with the addition of lactose additives which crystallize and lead to stronger bonds within the pellet.